3(x-10)+3(2-5)=5x-3

Simple and best practice solution for 3(x-10)+3(2-5)=5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-10)+3(2-5)=5x-3 equation:


Simplifying
3(x + -10) + 3(2 + -5) = 5x + -3

Reorder the terms:
3(-10 + x) + 3(2 + -5) = 5x + -3
(-10 * 3 + x * 3) + 3(2 + -5) = 5x + -3
(-30 + 3x) + 3(2 + -5) = 5x + -3

Combine like terms: 2 + -5 = -3
-30 + 3x + 3(-3) = 5x + -3

Multiply 3 * -3
-30 + 3x + -9 = 5x + -3

Reorder the terms:
-30 + -9 + 3x = 5x + -3

Combine like terms: -30 + -9 = -39
-39 + 3x = 5x + -3

Reorder the terms:
-39 + 3x = -3 + 5x

Solving
-39 + 3x = -3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-39 + 3x + -5x = -3 + 5x + -5x

Combine like terms: 3x + -5x = -2x
-39 + -2x = -3 + 5x + -5x

Combine like terms: 5x + -5x = 0
-39 + -2x = -3 + 0
-39 + -2x = -3

Add '39' to each side of the equation.
-39 + 39 + -2x = -3 + 39

Combine like terms: -39 + 39 = 0
0 + -2x = -3 + 39
-2x = -3 + 39

Combine like terms: -3 + 39 = 36
-2x = 36

Divide each side by '-2'.
x = -18

Simplifying
x = -18

See similar equations:

| 6f+10=60 | | 3x=5x+11 | | 12x-3-7x+8=11(-1-5x)-4(-4+6x) | | 1=5(t-6) | | -x-54=-7x+54 | | X+2+x+2+x+2+X+2=12 | | 1+x+4+x+7+x+10=0 | | 0.02(n-550)=105 | | 4p+3q=41 | | 12.6x=56.7 | | 6n=3n-2+2(2n+1) | | -6s-11=-2s+5 | | 9k-26=6k | | 2x+7-26=17-4x+5 | | 2xy+60-5xy=x+10+y | | -2p-6=10-10p | | 26+2x=263 | | x-32=63-4x | | 0=-X^2-6X | | 6x+8=46 | | 12x^2y+8xy+4xy^2= | | 5x+16=8x-8 | | 5x-306=20 | | 18+x=x+11+12 | | 2xy-x+40-y=5y-20+xy | | T=141.68+.75M | | -7+4m=6n-5 | | 37xsquared+35x-14= | | .2x-25=18 | | -38+3x=38-x | | 4x^2+15x-4=f(x) | | ryan=rike |

Equations solver categories